Double‐Edged Role of Resource Competition in Gene Expression Noise and Control. Issue 1 (8th February 2022) - Goetz, Hanah; Stone, Austin; Zhang, Rong; Lai, Ying‐Cheng; Tian, Xiao‐Jun
Abstract: Despite extensive investigation demonstrating that resource competition can significantly alter the deterministic behaviors of synthetic gene circuits, it remains unclear how resource competition contributes to the gene expression noise and how this noise can be controlled. Utilizing a two‐gene circuit as a prototypical system, a surprising double‐edged role of resource competition in gene expression noise is uncovered: competition decreases noise through introducing a resource constraint but generates its own type of noise which we name as "resource competitive noise." Utilization of orthogonal resources enables retainment of the noise reduction conferred by resource constraint while removing the added resource competitive noise. The noise reduction effects are studied using three negative feedback types: negatively competitive regulation (NCR), local, and global controllers, each having four placement architectures in the protein biosynthesis pathway (mRNA or protein inhibition on transcription or translation). The results show that both local and NCR controllers with mRNA‐mediated inhibition are efficacious at reducing noise, with NCR controllers demonstrating a superior noise‐reduction capability. Combining feedback controllers with orthogonal resources can improve the local controllers. This work provides deep insights into the origin of stochasticity in gene circuits with resource competition and guidance for developing effective noise control strategies. Abstract : Resource competition between synthetic gene circuits can significantly affect the circuit behaviors. It is found that resource competition has a double‐edged effect on protein noise levels. Orthogonal resources, negative feedback controllers, and their combination can be efficacious at reducing noise. The findings provide deep insights into the origin of stochasticity in synthetic gene circuits and effective noise control strategies.